6-3x=3x+1

Simple and best practice solution for 6-3x=3x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3x=3x+1 equation:



6-3x=3x+1
We move all terms to the left:
6-3x-(3x+1)=0
We get rid of parentheses
-3x-3x-1+6=0
We add all the numbers together, and all the variables
-6x+5=0
We move all terms containing x to the left, all other terms to the right
-6x=-5
x=-5/-6
x=5/6

See similar equations:

| x-32=17- | | 3n²+24n=48 | | 17-9y=-13+6y | | -12+7m=6m+10 | | 32+65+2x=180 | | 8+2m=m-10 | | w²+12w+32=0 | | a+4=89 | | 741=451(1+r)5 | | (2k)^2-4(2)(3k)=0 | | (3x–4)(3x+4)=8(5x–1)(5x–1) | | 5x+(x-2)=148 | | n=2,3,2.5,4 | | P=-0.5x^2+40x-740 | | –8−7c=–6c | | –8+4d=5d | | 5/6x=2/3x+4 | | x=0.5x+20 | | 5k-5=6 | | 3/8x-1/2x=3/4x-14=0 | | 15h+17=21 | | 15h​ +17=21 | | -4(x+3)=11 | | 3o-4=11 | | Y=7;x=49 | | −66=−3(2+5x)+5x | | 9x-6=12x+12 | | x*0.35=100 | | 3/8x-1/2x-3/4x+14=0 | | 2x+4x+9=12x-2x-3 | | 2m-14=8 | | 2x+4x+9=12x-2x3 |

Equations solver categories